Recent progress in the role of endogenous metal ions in doxorubicin-induced cardiotoxicity - Zhou, Ni; Wei, Shanshan; Sun, Taoli; Xie, Suifen; Liu, Jian; Li, Wenqun; Zhang, Bikui (Frontiers in Pharmacology, 2023)
Doxorubicin is a widely used anticancer drug in clinical practice for the treatment of various human tumors. However, its administration is associated with cardiotoxicity.Administration of doxorubicin with low side effects for cancer treatment and prevention are, accordingly, urgently required. The human body harbors various endogenous metal ions that exert substantial influences. Consequently, extensive research has been conducted over several decades to investigate the potential of targeting endogenous metal ions to mitigate doxorubicin's side effects and impede tumor progression. In recent years, there has been a growing body of research indicating the potential efficacy of metal ion-associated therapeutic strategies in inhibiting doxorubicin-induced cardiotoxicity (DIC). These strategies offer a combination of favorable safety profiles and potential clinical utility. Alterations in intracellular levels of metal ions have been found to either facilitate or mitigate the development of DIC. For instance, ferroptosis, a cellular death mechanism, and metal ions such as copper, zinc, and calcium have been identified as significant contributors to DIC. This understanding can contribute to advancements in cancer treatment and provide valuable insights for mitigating the cardiotoxic effects of other therapeutic drugs. Furthermore, potential therapeutic strategies have been investigated to alleviate DIC in clinical settings. The ultimate goal is to improve the efficacy and safety of Dox and offer valuable insights for future research in this field.